A function f ( n ) , defined for all n ∈ N , is such that
f ( 1 ) + f ( 2 ) + ⋯ + f ( n − 1 ) + f ( n ) = n 2 f ( n )
If f ( 1 ) = 3 6 , calculate the value of f ( 8 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that ( n + 1 ) 2 f ( n + 1 ) = j = 1 ∑ n + 1 f ( j ) = j = 1 ∑ n f ( j ) + f ( n + 1 ) = n 2 f ( n ) + f ( n + 1 ) so that ( n + 2 ) f ( n + 1 ) = n f ( n ) and so ( n + 1 ) ( n + 2 ) f ( n + 1 ) = n ( n + 1 ) f ( n ) n ≥ 1 It is now a simple induction to show that f ( n ) = n ( n + 1 ) 7 2 for all n ≥ 1 , and hence that f ( 8 ) = 1 .
Problem Loading...
Note Loading...
Set Loading...
Let S n = k = 1 ∑ n f ( k ) . We can calculate f ( n ) using f ( n ) = n 2 − 1 S n − 1 . And we get f ( 2 ) = 1 2 , f ( 3 ) = 6 , f ( 4 ) = 3 . 6 ... and that f ( 1 ) f ( 1 ) = 1 , f ( 2 ) f ( 1 ) = 3 , f ( 3 ) f ( 1 ) = 6 , f ( 4 ) f ( 1 ) = 1 0 ... implying that f ( n ) f ( 1 ) = T n = 2 n ( n + 1 ) , where T n is the n th triangular number. Let us prove that the claim f ( n ) = n ( n + 1 ) 2 f ( 1 ) is true for all n ≥ 1 .
S n = k = 1 ∑ n f ( k ) = k = 1 ∑ n k ( k + 1 ) 2 f ( 1 ) = 2 f ( 1 ) k = 1 ∑ n ( k 1 − k + 1 1 ) = 2 f ( 1 ) ( 1 − n + 1 1 ) = n + 1 2 n f ( 1 ) = n ( n + 1 ) 2 n 2 f ( 1 ) = n 2 f ( n )
Proving that f ( n ) = n ( n + 1 ) 2 f ( 1 ) satisfies the equation S n = n 2 f ( n ) . Therefore, f ( 8 ) = 8 ( 8 + 1 ) 2 ( 3 6 ) = 1 .